Exploring the Routine Administration of Decision Aids for Palliative Chemotherapy to Patients by Nurses: A Qualitative Study Among Nurses and Oncologists. Issue 4 (July 2015) - Oostendorp, Linda J. M.; Ottevanger, Petronella B.; van der Graaf, Winette T. A.; Peters, Marlies E. W. J.; Hermens, Rosella P. M. G.; Stalmeier, Peep F. M.
Abstract : Background: Decision aids (DAs) effectively support patient decision making but are rarely used in daily practice. Objective: To explore nurses' and oncologists' views on routinely offering DAs on palliative chemotherapy to patients by nurses. Most interviewees had clinical experience with the DAs, which were booklets administered to patients by nurses. Methods: The study was guided by 3 theoretical implementation models of innovations in clinical practice, including factors related to the innovation, the professionals (nurses and oncologists), the patient, and the organization. Semistructured interviews were conducted among 12 nurses and 14 oncologists. Interviews were audio taped and fully transcribed. Results: The main barriers to routinely offering DAs to patients were found in nurses' and oncologists' opinions and attitudes (eg, concerns about the impact in this vulnerable population) and in the logistics of organizations (eg, the decision is already made before the nurse sees the patient). Twenty-two of 26 interviewees were open to the future use of the DAs. Disseminating information to professionals (eg, about positive effects of DAs) and embedding DAs in the existing workflow would facilitate implementation. Conclusions: Most nurses and oncologists were open to the future use of the DAs by nurses, provided that certain barriers, particularly related to professionals' opinions and attitudes and logistical procedures in the organization, could be overcome. Implications for Practice: These findings can inform a tailored strategy to implement DAs on palliative chemotherapy. Implementation should start with interventions to motivate professionals, for example, educational meetings.